The Effect of Giving Biscuits Made from Haruan Fish Flour and Yellow Pumpkin on the Nutritional Status of Toddlers - Ratnawati, Ratnawati; Satriani, Satriani (Media Publikasi Cendekia Indonesia, 2024)
This study aims to investigate the effect of biscuits made from haruan fish flour and yellow pumpkin on the nutritional status of toddlers in the working area of Puskesmas Mangkupalas. A quasi-experimental pre-post test with control group design was employed, with a single-blind approach. The study was conducted from September to November 2021. A total of 22 toddlers were selected using purposive sampling. Respondents were divided into two groups: the intervention group, which received biscuits made from haruan fish and yellow pumpkin flour, and the control group, which received government-provided biscuits. Data on energy and protein intake were collected using a Food Recall, and nutritional status was assessed based on Weight-for-Age index using anthropometric measurements. In the control group, the average Z-score before the intervention was -1.4345 (normal nutritional status), which increased to -1.3536 post-intervention (still normal). The intervention group had an average Z-score of -2.0009 before the intervention, which decreased to -2.1691 (indicating moderate malnutrition). The control group's average energy intake was 956.864 kcal before the intervention and 792.564 kcal during the intervention. In the intervention group, energy intake was 1010.891 kcal before and 793.109 kcal during the intervention. Protein intake in the control group was 34.436 g before the intervention and decreased to 31.691 g during the intervention. The intervention group saw an increase from 38.164 g to 58.75 g. The intervention with biscuits made from haruan fish flour and yellow pumpkin flour did not significantly affect the nutritional status or energy and protein intake of the toddlers.